Bringing brain research into classroom practice (Utah : Linton Professional Development Corporation, 1997)
Elementary, middle, and high school examples
program 1 How the brain works while learning - program 2 bringing learning into long-term memory - program 3 an enriched environment for learning
Presenter: Pat Wolfe
Keywords: Effective teaching; Learning